Outcomes of thrombus aspiration during primary percutaneous coronary intervention for ST-elevation myocardial infarction - Rajakariar, K.; Andrianopoulos, N.; Gayed, D.; Liang, D.; Backhouse, B.; Ajani, A.E.; Duffy, S.J.; Brennan, A.; Roberts, L.; Reid, Christopher; Oqueli, E.; Clark, D.; et al. (WILEY, 2023)
Background: Previous large multi-centre randomised controlled trials have not provided clear benefit with routine intracoronary thrombus aspiration (TA) as an adjunct to primary percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI). Aim: To determine whether there is a difference in outcomes with the use of manual TA prior to PCI, compared with PCI alone in a cohort of patients with STEMI. Methods: We analysed data from 6270 consecutive patients undergoing primary PCI for STEMI prospectively enrolled in the Melbourne Interventional Group registry between 2007 and 2018. Multivariable analysis was performed to determine predictors of 30-day major adverse cardiovascular and cerebrovascular events (MACCE) and long-term mortality. Results: We compared 1621 (26%) patients undergoing primary PCI with TA to 4649 (74%) patients undergoing PCI alone. Male gender (81% vs 78%; P < 0.01), younger age (61 vs 63 years; P = 0.03), GP-IIb/IIIa use (76% vs 58%, P < 0.01), and current smoking (40% vs 36%; P < 0.01) were more common in the TA group. TA was more likely to be used in patients with complex lesions (83% vs 66%; P < 0.01) with TIMI 0 flow (77% vs 56%; P < 0.01). No significant difference in post-procedural TIMI flow, stroke, 30-day mortality, or long-term mortality were identified. Multivariable analysis demonstrated a reduction in 30-day MACCE (hazard ratio (HR) 0.75; confidence interval (CI) 0.63–0.89; P < 0.01) in the TA group, but was not associated with long-term mortality (HR 0.98; CI 0.85–1.1; P = 0.73). Conclusion: The use of TA in patients undergoing primary PCI for STEMI was not associated with improved short or long-term mortality when compared with PCI alone.